La revocatoria inesperada del mandato a las autoridades de los Gobiernos Autónomos Descentralizados afecta a la colectividad y a la actividad de la administración pública - Villalva Martínez, Patricia Teresa (2015)
The recall of so synthesized, is only the right of all citizens enjoy political rights in our Constitution of the Republic of Ecuador, taking into account the sovereignty that weighs on citizens, to stop to put Somehow the president in question, its administration and management, through popular democracy.This type of actions taken by citizens of a particular jurisdiction, in most cases do so because their authority has not fulfilled its work within the civil service effectively and efficiently, or work plan offered in campaign or proven cases of corruption or simple political rivalry. The revocation process takes them through a thorough process, through the collection of signatures supporting the measure, taking into account the number to be reached depending on their jurisdiction and, once approved this point and acceptance of the competent authority begin the voting process where people choose whether to continue with its mandate or simply removed from office, making an immediate application results. We must take into account that this right has a double face, or calling attention to improving the quality of work within the administration or simply replacing the revoked authority is worse than the previous one would be talking about that citizenship plays all or nothing, because it is the central role of citizenship that counts in such processes, in them is the future. Must be borne in mind that this is not a whim or political rivalry, now this last year was a number of approaches to different authorities revocation throughout Ecuador, which is why the government of the day, put limitations to the new procedure regarding the application and processing. Likewise take a fundamental role to sleep part of these processes such as media, which have to be biased in terms of approach and to present the truth to the public in a mature way to make a decision, which not only has to do with its own benefits but a conglomerate in general, and that is being debated for the advancement not only of territory but also the citizens who live in it and of those to come